Influence of metal matrix powder size on the tensile strength of a SiCp/AlSi7Mg0, 6 composite produced by field assisted sintering technique. Issue 1 (May 2021) - Pippig, R; Hirsch, S J; Grund, T; Lampke, T
Abstract: In the present study, 35vol% SiCp /AlSi7Mg0, 6 composites were prepared using field assisted sintering technique in order to investigate the effect of different particle fractions and size distributions of the AlSi7Mg matrix powder on the tensile properties of the produced composite material. In most usecases the size of the reinforcement phase is given by the application and is only variable within narrow limits (< 20pm particle size in this work). On the other hand, there is potential for optimization of the matrix powder. In this investigation, fine (d50 = 25 µm), coarse (d50 = 52 µm), bimodal (50wt% of fine + 50wt% of coarse, d50 = 36 µm) and as received (d50 = 40 µm) aluminum powder was used as the matrix powder. Using fine matrix powder has improved yield strength by 5 % and ultimate tensile strength by 7 % compared to the as received condition. This is largely due to the lower porosity of the composite produced under the use of the fine matrix powder ((0.07 ± 0.04) %) in contrast to the composite using the as received aluminum powder ((0.62 ± 0.35) %). At the same time, the consumed heating energy of the composite was decreased by almost a third when using the fine matrix powder in comparison to the use of the as-received matrix powder. This paper presents results of an optimization approach for mechanical properties of aluminum matrix composites without any changes of the sintering parameters.